NF2-related Schwannomatosis and Gorlin Syndrome - Evans, D. Gareth R. (Henry Stewart Talks, 2024)
Neurofibromatosis Type 2 (NF2), Vestibular schwannoma, Meningiomas, NF2 symptoms in children and adults, Using MRI in NF2 diagnosis, Gorlin syndrome, Basel Cell Carcinoma (BCC), Gorlin syndrome gene identification, Pre- and post-cancer register use